If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 9 = 3(m + -5) + 7 Reorder the terms: 9 + m = 3(m + -5) + 7 Reorder the terms: 9 + m = 3(-5 + m) + 7 9 + m = (-5 * 3 + m * 3) + 7 9 + m = (-15 + 3m) + 7 Reorder the terms: 9 + m = -15 + 7 + 3m Combine like terms: -15 + 7 = -8 9 + m = -8 + 3m Solving 9 + m = -8 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 9 + m + -3m = -8 + 3m + -3m Combine like terms: m + -3m = -2m 9 + -2m = -8 + 3m + -3m Combine like terms: 3m + -3m = 0 9 + -2m = -8 + 0 9 + -2m = -8 Add '-9' to each side of the equation. 9 + -9 + -2m = -8 + -9 Combine like terms: 9 + -9 = 0 0 + -2m = -8 + -9 -2m = -8 + -9 Combine like terms: -8 + -9 = -17 -2m = -17 Divide each side by '-2'. m = 8.5 Simplifying m = 8.5
| -4=3.5-1.5y | | 8m=5m+1 | | 5x+7=-3x-5 | | 4x^4+19x^2-5x+3=0 | | x=8x-50 | | 2(2y-3)=9-2y | | y=.50x-3 | | 3x-8y=27 | | (x^2+8x-7)(9x^2-8x+8)= | | x+2x=880000 | | .33-.03(x+1)=-.05(2-x) | | 2/3n-n/6 | | 4x^3-12x=1 | | 5x^3-2x^2-15x+6= | | -3y+9=-3(2y+2) | | y/2+y/2=31 | | 11x+24=4x+143 | | 6/5p=-24 | | 199-7x=38x+24 | | 6/5x=-24 | | 1/3x+2/3-5/3x | | 5x^2+12x+15=0 | | (64x^10y^10)^(1/2) | | (64x^10y^10)^1/2 | | 10^5/10^-7 | | 9(5X-3)=46X | | (n-2)180=1980 | | 11.97+v=5v-.11 | | (n-2)180=1989 | | y^2=2*x+1 | | 28x-28=28 | | n-2(180)=1980 |